Teaching Implementation of MOOC and Flipped Classroom - Zhang, Fan; Feng, Shuxiong (Advances in Social Sciences Research Journal, 2019)
The paper introduced the construction of flipped classroom teaching model based on MOOC. It discussed the overall lesson preparation and class guidance, then analyzed how evaluate teaching effect. It shed light on changing teaching concepts, course arrangement of College English, cooperative teaching, and learning successful experience of MOOCs. Then it indicates application strategies of MOOCs in college English teaching. Future implications of implementations of the teaching model are also discussed.